Evaluation of Antibiofilm and Cytotoxic Activity of Microalgae Isolated from Different Sites of betwata- Erbil/Iraq (Baghdad Science Journal, 2024)
This in vivo study is aimed to assess the antibiofilm and cytotoxic potential of selected microalgae isolates. Different concentration of microalgal isolates used for each of antibiofilm and cytotoxic studies. A total extract of 10 μL MTT was added to each well with LB broth, plates were read using microtiter plate spectrophotometer at 490 nm and 630 nm, respectively. The cell viability was determined in CCD-18℃ cells (3x103 cells/well) by MTT assay at 590 nm.   The microalgae isolates showed antibiofilm affect after 48 hrs on Pseudomonas aeruginosa PA01 and this effect was observed to be higher than those of S. aureus. Chlorella sp. which showed the maximum antibiofilm activity while Arthrospira platensis had no biofilm inhibition activity. Chlorella sp. inhibited about 82.67% of the biofilm at 5 mg/mL concentration. Moreover, the antibiofilm effects of Chara sp. and Spyrogyra sp.1 reached 79.01% and 76.31% at 1 mg/mL, respectively. Among all microalgal isolates, a moderate inhibitory effect was observed on Pseudomonas aeruginosa biofilm with Chlorella sorokiniana. Cell viability was not changed significantly at higher doses extracts. More than 73% of the cells were viable in all concentration of the algae extracts.  All of the microalgal samples were found to have biofilm inhibition activity. The findings suggested that future development of microalgal samples as a means of inhibiting Pseudomonas aeruginosa biofilms is possible. Colonic epithelial cells may become cytotoxic in response to algae extracts. Further research is necessary to verify that extracts are safe for human consumption, which may have been hypothesized.